PENGEMBANGAN PERANGKAT PEMBELAJARAN TOPIK LINGKARANBERBASIS KECERDASAN MAJEMUK GARDNER BERORIENTASI PADA PRESTASI DAN KEMANDIRIAN BELAJAR - Melissa, Margaretha Madha (Widya Warta, 2016)
The aim of this research is to develop the circle instructional kits in 8th grade on 2nd semester based on Gardner's multiple intelligence oriented to students’ achievement and self-regulated learning in mathematics which has a good quality.theoryThe instructional kits in this research are consists of lesson plans and students’ worksheets which has validity, practicality, and effectiveness criteria. The developing model was ADDIE’s model (Analysis, Design, Development, Implementation, and Evaluation). The analysis of the validity and practicality of the data was done by converting the quantitative data in the form of assessment result score into the qualitative data in the form of five scales. The analysis of the effectiveness of the test results was conducted by determining the percentage of the students’ learning mastery. The assessment of self-regulated mathematics learning questionnaires was conducted by determining the percentage of the students for each category. The result of the validation shows that lesson plans and students’ worksheets valid in a very good category. The lesson plans and students’ worksheets are practical in a very good category based on teachers’ assessment and the implementation of learning, a good category based on students’ assessment. Instructional kits also effective based on students’ mathematics achievement and self-regulated learning.The percentage of the students who completed the mathematics achievement test is 88.86%. The total score of the final students’ self-regulated learning questionnaires is more thanthat of the early students’ self-regulated learning questionnaires and the percentage of the students who achieved minimal high category is 96%.